Implementasi Putusan Pengadilan Agama Purwakarta mengenai Kewajiban Ayah atas Hak Nafkah Anak Pasca Perceraian - Sofia Gussevi; Ira Novianty; Pebi Supiana (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2023)
This research departs from the phenomenon in the field that the child's income after the divorce of his parents is often very unprofitable for the child. There are no technical and strict regulations or provisions regarding procedures for providing child support, this results in the survival of children who are victims of divorce. This study aims to explain the legal basis for the decisions and considerations of the Purwakarta Court judges regarding the obligation of fathers for child support after divorce and finally, the efforts of the Purwakarta Religious Court to provide post-divorce child support. The methodology used in this research is descriptive qualitative. Based on the results of the study, it can be concluded that the efforts of the Purwakarta Religious Court in providing children's post-divorce rights are carried out by providing information to the parties to include the demandsReligious for children's livelihood rights along with iddah and mut'ah livelihoods in the divorce lawsuit. To guarantee children's livelihood rights, the Purwakarta Religious Court cooperates with the husband's place of work to make direct deductions from the husband's income, but this has not been implemented.